Pengaruh Likuiditas, Leverage Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Sub Sektor Pertambangan Batu Bara Yang Terdaftar Di Bursa Efek Indonesia - Kosim, Belliwati; Safira, Maya (Universitas Muhammadiyah Palembang, 2020)
Purpose - This research aimed to find outthe effect of liquidity, leverage, and profitability on stock prices in coal mining sub-sector companies listed on the Indonesia Stock Exchange.Design/methodology - For sampling using non-probability sampling with a purposive sampling method, the sample was used 12 companies. The data was needed secondary data obtained from the Indonesia Stock Exchange through the website www.idx.co.id and for collection data used the method. The analysis technique used in this study was multiple linear regression analysis, classic assumption test, and hypothesis testing.Findings - For sampling using non-probability sampling with a purposive sampling method, the sample was used 12 companies. The data was needed secondary data obtained from the Indonesia Stock Exchange through the website www.idx.co.id and for collection data used the method. The analysis technique used in this study was multiple linear regression analysis, classic assumption test, and hypothesis testing. The results of the study of multiple linear regression Y = -1,651 + 0.594 (X_1) + 0.0760 (X_2) + 0.517 (X_3), F test (simultaneous test) with F_count18.445> F_table 2.77 or significant F 0.000 < ? 0.05 means that there was a significant influence of liquidity, leverage, and profitability simultaneously on stock prices and t test (partial test) on liquidity t_count22.267> t_table 2.0024 and significant liquidity 0.027 <? 0.05, this showed that there was a partial effect of liquidity on stock prices. At profitability t_count 6,070> ttable 2.0024 and significant leverage of 0.855> 0.05 this indicates that there was no partial leverage effect on stock prices and significant profitability of 0,000 <0.05 this indicates that there was a partial effect of profitability on stock prices while the leverage tcount = 0.183 <ttable 2.0024